Grain-boundary segregation of boron in high-strength steel studied by nano-SIMS and atom probe tomography. (1st January 2020) - Da Rosa, G.; Maugis, P.; Portavoce, A.; Drillet, J.; Valle, N.; Lentzen, E.; Hoummada, K.
Abstract: High resolution imaging by secondary ion mass spectrometry and atom probe tomography have been employed to investigate boron segregation at austenite grain boundaries (γGBs) after soaking in a high-strength low-carbon steel. The combined use of these two analytical techniques is shown to be powerful for quantifying solute and segregated boron levels. Quenching was performed after soaking aiming to clarify the temperature effect on boron distribution under thermal equilibrium. Boron depletion in the γGBs vicinity was observed in the as-quenched states from high temperatures, suggesting that the cooling rate was not fast enough to limit boron diffusion during cooling. We found that boron segregation at γGBs increases with temperature. This is due to the increase of solute boron concentration in the grains, resulting from boride precipitate dissolution. It appears that the segregation magnitude still follows the equilibrium laws as a function of temperature. From our investigations, it was possible to determine the boron equilibrium segregation enthalpy. These results have important practical consequences for controlling the levels of segregated boron in steels. Graphical abstract: Image, graphical abstract